Seaport-inland port dyad dynamics: an investigation of service provisions and intermodal transportation linkages. Issue 3 (2015) - Roso, Violeta; Russell, Dawn; Ruamsook, Kusumal; Stefansson, Gunnar
This research investigates the operational and logistical dynamics of seaports and inland ports. Face-to-face semi-structure interviews were conducted on three seaport-inland port dyads that actively use intermodal transportation to move freight between the seaports and connected inland ports. The three dyads are the port of Virginia and Virginia Inland Port (VIP) in the USA, the Port of Sydney and Minto terminal in Australia, and the Port of Gothenburg and Hallsberg terminal in Sweden. Findings of this research provide essential understanding of the range of services provided at the three inland ports studied, offering a benchmark for ports around the world in devising their business portfolio.